Learning Physics using Online Learning during the Covid-19 Pandemic - Laxmi Zahara; Khaerus Syahidi; Fartina Fartina; L. Gede Sudarman (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2021)
The Indonesian government has designated COVID-19 as a type of disease that causes public health emergencies. Thus the Ministry of Education and Culture through Circular Number 4 of 2020 ordered that the implementation of learning take place from home online. This study aims to determine the implementation of distance learning at SMAN 2 Masbagik, obtain an overview of the implementation of the teaching and learning process and find solutions during the COVID-19 pandemic. This research method uses survey research. The population of this study were all students of SMAN 2 Masbagik. The research sample of class X and XI students, amounting to 202 students. This study uses survey research using the google form application. The results of this study are, 1) 96% of students have studied online; 2) 95.5% of students stated that the implementation time was in accordance with the schedule determined by the school; 3) 55.4% of students stated that the information obtained through online learning was good; 4) 88.1% of students stated that the application used online was the Whats app; 5) 40.6% of students stated that online learning made the guidance process easier; 6) 63.9% of students stated that the learning constraint of g was a limited quota, 33.2% of students stated that the problem was a piling up of tasks and 30.2% of students stated that the network was not stable; 7) 35% of students stated that online learning barriers were quite influential on their psychological conditions and 30.2% stated that they had an effect. Thus it is hoped that at SMAN 2 Masbagik, training will be held for all teachers related to online learning such as the google classroom application, quiziz, kahoot and microsof 365, schools provide free quota for teachers at SMAN 2 Masbagik, teachers do not overload students with assignments and require supervision of online learning process carried out by teachers in their respective classes to expedite the learning process.